Design of Teaching Materials for Hybrid Electric Vehicles Fundamentals in Vocational Education: a Systematic Literature Review - A Syaefudin Siswanto; Ida Hamidah (Journal of Vocational Education Studies, 2026)
Transition toward electric vehicles creates new demands for vocational education, particularly in preparing students with Hybrid Electric Vehicle (HEV) competencies. Although crucial, structured and pedagogically based HEV fundamental teaching materials remain underexplored. This study analyzes global research trends in designing HEV teaching materials through a Systematic Literature Review (SLR) of 25 international studies published over the last two decades. Analysis focuses on three main aspects: (1) global development trends of HEV teaching materials, (2) digital technologies utilized in their development, and (3) the most frequently taught fundamental HEV concepts in vocational education. The results show a developmental trend shifting toward integrating digital project-based learning and simulations to facilitate complex conceptual understanding. Dominant digital technologies include virtual laboratories & experimental platforms (48%), interactive multimedia & simulation-based learning (28%), and e-learning & digital curriculum systems (24%), which are proven to increase learning interactivity and effectiveness. The most frequently taught concepts cover powertrain architecture & configuration (24%), energy management & control strategies (16%), and vehicle dynamics & performance (16%). Pedagogically, these materials are integrated through Project-Based Learning (PBL), simulation-based instructions, and direct laboratory experiences, aligning with competency-based vocational education. This study concludes that the future of HEV education relies on the synergistic integration of digital technology, authentic problem-solving, and multidisciplinary collaboration. This integration enhances conceptual understanding and applied technical competencies, supporting the broader goal of sustainable automotive education in the electrification era.